RECONCILIATION AS AN EFFORT TO FORM A PEACEFUL (SAKINAH) FAMILY IN ISLAMIC LAW REVIEW - Abdul Aziz; Tirmidzi Tirmidzi (USRAH: Jurnal Hukum Keluarga Islam, 2021)
In a marriage life, of course, there are some problems that trigger disputes, such as economic problems, emotions, heredity or education. These problems become the cause of divorce between husband and wife. At the time of divorce, the wife is still in the period of iddah and that time can be used by her husband to refer back to himself. Therefore, this paper aims to know the opinion of imam madhhab about reconciliation, to know the problems that cause divorce, and to know the wisdom of reconciliation and the peaceful (sakinah) family.The method used in this study uses literature research or research called Library research, namely research of various reading materials, such as scientific journals, books, dan written works others related to the problems studied namely about refer as an effort to form a peaceful (sakinah) family in Islamic law review.The discussion of the scholars differs on the validity of a husband who wants to reconcile to his wife who is being accused of minor divorce (Talaq Raj'i) with deeds. Some allow (validate) the reconciliation, some validate but the intention should be clear and some do not validate at all reconciliation with deeds, but ones should recite it sarih (clear) and kinayah (satire). Regardless and differences of opinion, it would be nice if the implementation of refer enabled to give the opportunity to the husband and wife to repair the relationship that has been cracked, so that they can be whole again into a family that is sakinah, mawadah, warahmah as a goal and marriage without the intention to hurt their partner again.Keywords: reconciliation, sakinah family, and Islamic law